2017
DOI: 10.22270/jddt.v7i6.1542
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Potential Drug - Drug Interactions in Medicine Department of a Multi Specialty Teaching Hospital

Abstract: Aim of study: Drug-drug interaction (DDI) occurs when two or more drugs are simultaneously administered, where the effect of one drug is altered by the concomitant use of another drug. The prospective observational study aimed to assess the potential drug-drug interactions (pDDIs) in general medicine department of a multispecialty teaching hospital. Material & Methods: Data of all the patients admitted in the general medicine department was collected and analyzed for drug-drug interactions by using drug inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Study revealed very high prevalence of drug-drug interactions in the cardiac in-patients as supported by other studies. [4][5][6][7] The high prevalence may be due to presence of various risk factors in hospitalized patients. Elderly age group, cardiac illness and associated multiple co-morbidities which in turn lead to polypharmacy, may result into development of drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study revealed very high prevalence of drug-drug interactions in the cardiac in-patients as supported by other studies. [4][5][6][7] The high prevalence may be due to presence of various risk factors in hospitalized patients. Elderly age group, cardiac illness and associated multiple co-morbidities which in turn lead to polypharmacy, may result into development of drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…8 Majority of drug interactions reported in the study were of moderate to major severity as also seen in various other studies. 6,7 (Table 2). Also, the documentation status varied from fair to good evidence.…”
Section: Discussionmentioning
confidence: 99%